Database Performance Optimization using Lazy Loading with Redis on Online Marketplace Website - Suryawan, Albertus Ivan; Muliantara, Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 3 (2024): JELIKU Volume 12 No 3, February 2024, 2024)
With the pandemic lasting over 2 years, many businesses start to adapting a digital approach of their business to stay alive. While in the same time, a number of users of digital platform also skyrocketed due to physical contact restriction policy. This causes a performance hit toward several online services such as an online marketplace due to high network traffic from many users accessing it in the same time, including latency issues. In this research, the authors try to implement an application-level caching with an in-memory database, Redis, using Lazy Loading approach. Beside implementing caching, authors also compare the performance of using cache and not using cache by load testing both implementation using similarly built application. Based on the result, there is a performance gain of 38-65% based on the load and scenario by using application-level caching